Separate aneurysmal neck is essential for analyzing hemodynamics and predicting instability of intracranial aneurysms - Yudi Tang; Haining Wei; Zihao Zhang; Mingzhu Fu; Junqiang Feng; Zhixin Li; Xinke Liu; Yue Wu; Jinyuan Zhang; Ting Chen; Wei You; Rong Xue; et al. (Annals of Medicine, 2025)
Background Hemodynamics influence aneurysm growth and rupture through injury and inflammation mediated by both high and low wall shear stress (WSS). The parent artery configuration (bifurcation or sidewall) significantly impacts hemodynamics at the aneurysmal neck, yet this factor has been overlooked in hemodynamics-based aneurysm risk assessment. This study aimed to evaluate the effect of parent artery type on the relationship between aneurysmal neck WSS and inflammation.Methods Fifty-six unruptured intracranial aneurysms from 55 participants were prospectively analyzed. Imaging was performed using 7.0 T MRI. The aneurysm-to-pituitary stalk contrast ratio (CRstalk) quantified aneurysm inflammation and instability. Hemodynamic parameters were assessed using four-dimensional (4D) flow MRI.Results The hemodynamic characteristics of the aneurysmal neck, as related to CRstalk, differed from those of the whole aneurysm. Most aneurysmal necks exhibited a significant negative correlation between WSS and CRstalk in the bifurcation group (p = 0.004) and a significant positive correlation in the sidewall group (p = 0.010). Twenty-three aneurysms showed inconsistent WSS-CRstalk correlations between the whole aneurysm and the neck region.Conclusion The location of an aneurysm (bifurcation or sidewall) significantly influences the correlation between WSS and CRstalk specifically at the aneurysmal neck. Regional hemodynamic assessment of the neck provides a novel approach for improving rupture risk prediction.